Isolation and Screening of Endophytic Fungi from Soursop (Annona muricata L.) Leaves: Potential Sources of Antimicrobial Compounds - Nurhaida, Nurhaida; Murniana, Murniana; Amrina, Bella Septie; Rasyid, Syarifah AB (Universitas Syiah Kuala, 2023)
Endophytic fungi, which reside within plant tissues, offer a unique ecological perspective due to their mutually beneficial relationship with host plants. Soursop (Annona muricata L.) leaves, known for their medicinal properties, contain bioactive compounds that may be produced by endophytic fungi. This study aimed to isolate endophytic fungi from soursop leaves and evaluate their potential as antimicrobial compound producers. Twenty endophytic fungal isolates were obtained from soursop leaves using Potato Dextrose Agar (PDA) supplemented with leaf extract. Out of these isolates, eight demonstrated antimicrobial activity against the tested microorganisms. Notably, the extract produced by SLE16 exhibited inhibitory effects against Gram-negative bacteria, while isolates SLE7, SLE8, and SLE14 showed antifungal activity against Candida albicans. Furthermore, isolates SLE18, SLE19, and SLE20 displayed significant inhibition of Trichophyton rubrum growth. The extracellular extracts derived from these endophytic fungi exhibited hydrophilic properties and formed inhibition zones larger than 15 mm, indicating their potential as antimicrobial compounds. These findings highlight the potential of endophytic fungi isolated from soursop leaves as valuable sources of novel antimicrobial compounds